Exploration of Implementation Variables Impacting Trauma Informed Practices in Schools: A Narrative Review - Rachel A Parker; David Hodgson; Lisa Wood; Karen Martin (International Journal of School Social Work, 2022)
Current literature suggests that by using trauma- informed practices (TIP) in our schools and classrooms, positive short and long-term outcomes can be achieved for both children and their communities. However, there is little research identifying what helps or hinders the implementation of trauma-informed practice in schools or the development of a practitioner’s trauma-informed pedagogy. As part of this narrative review, 25 trauma- informed practice implementation variables were identified from 34 peer-reviewed works of current (2015-2020) literature using a process of thematic analysis. This review utilised an ecological model as an overlay to present these variables in a useable format. The results of this research may be utilised to identify unaddressed implementation variables that support practice change and TIP in schools. The literature and this review support the idea that, if given the right input, conditions and setting events, an effective trauma-informed practice or pedagogy can be developed. Furthermore, by helping practitioners fill the gaps in their knowledge and assisting them to develop their trauma-informed pedagogy, they are able to create an environment where students who have experienced complex trauma may be healthy, safe, engaged, and supported.
Keywords: Trauma informed practice; implementation variables; ecological framework; trauma informed practice in schools; trauma informed practice change.